A Note on Limit Shapes of Minimal Difference Partitions - Comtet, Alain; Majumdar, Satya N.; Sabhapandit, Sanjib (Журнал математичної фізики, аналізу, геометрії, 2008)
We provide a variational derivation of the limit shape of minimal difference partitions and discuss the link with exclusion statistics.Mathematics Subject Classification: 05A17, 82B44.